The impact of vaccination and prior exposure on stool shedding of Salmonella Typhi and Salmonella Paratyphi in 6 controlled human infection studies - Gibani, M; Voysey, M; Jin, C; Jones, C; Thomaides-Brears, H; Jones, E; Baker, P; Morgan, M; Simmons, A; Gordon, M; Cerundolo, V; Pitzer, V; et al. (Oxford University Press, 2018)
Background: Shedding of Salmonella Typhi or Paratyphi in the stool or urine leads to contamination of food or water, which is a prerequisite for transmission of enteric fever. Currently, there are limited data on the effect of vaccination or prior exposure on stool shedding. Methods: Six Salmonella Typhi or Paratyphi human challenge studies were conducted between 2011 and 2017. Participants were either unvaccinated or vaccinated with 1 of 4 vaccines: Vi-polysaccharide (Vi-PS), Vi-tetanus-toxoid conjugate vaccine (Vi-TT), live oral Ty21a vaccine, or an experimental vaccine (M01ZH09). Daily stool cultures were collected for 14 days after challenge. Results: There were 4934 stool samples collected from 430 volunteers. Participants who received Vi-PS or Vi-TT shed less than unvaccinated participants (odds ratio [OR], 0.34; 95% confidence interval [CI], 0.15–0.77; P = .010 and OR, 0.41; 95% CI, 0.19–0.91, P = .029 for Vi-PS and Vi-TT, respectively). Higher anti-Vi immunoglobulin G titers were associated with less shedding of S. Typhi (P < .0001). A nonsignificant reduction in shedding was associated with Ty21a vaccine (OR, 0.57; 95% CI, 0.27–1.20; P = .140). Individuals previously exposed to S. Typhi shed less than previously unexposed individuals (OR, 0.30; 95% CI, 0.1–0.8; P = .016). Shedding of S. Typhi was more common than S. Paratyphi. Conclusions: Prior vaccination with Vi vaccines, or natural infection, reduces onward transmission of S. Typhi. Field trials of Vi-TT should be designed to detect indirect protection, reflecting the consequence of reduced stool shedding observed in the human challenge model.